A redescription of Chaetonotus (Primochaetus) veronicae Kånneby, 2013 (Gastrotricha: Chaetonotidae) - Kånneby, Tobias (Zootaxa, 2015)
Gastrotricha are microscopic metazoan animals common to both freshwater and marine environments. A re-examination of Chaetonotus (Primochaetus) veronicae Kånneby, 2013, described from northern Sweden, revealed an important diagnostic character (bifurcated spines) that had been overlooked in the original description (Kånneby 2013).